One new species of the genus Guihaia J. Dransf. et al. (Arecaceae Schutz.-Sch) for the flora of Vietnam - Anh, Tran Phuong; Khoi, Nguyen Khac (Academia Journal of Biology, 2014)
The genus Guihaia has been just published in 1985 by J. Dransfiel et al., after studying specimens of the genera Trachycarpus and Rhapis. There were only 2 species in this genus, such as G. argyrata (Lee & Wei) Lee, Wei & J. Dransf. and G. grossefibrosa (Gagnep.) J. Dransf., Lee & Wei, distributed in China and Vietnam. According to documents, there was only G. grossefibrosa in the flora of Vietnam, which was listed in the Red Data Book of Vietnam. During the specimen study, we have introduced G. argyrata (typus of the genus) as a new record for the flora of Vietnam. The specimens were collected in the Caobang and Langson provinces. So that, the genus Guihaia J. Dransfiel et al. in Vietnam has 2 species.